Early enteral versus early parenteral nutrition in critically ill patients with respiratory distress: a case-control study - Basant Salah El Meligy; Seham Awad El-sherbini; Mohamed Mosaad Soliman; Heba Mohamad abd El-Ghany; Elshimaa Salah Ahmed (SpringerOpen, 2023)
Abstract Background Nutritional support is essential as enteral or parenteral nutrition to reduce catabolism, to lower the complications rate, and to improve outcomes in critically ill patients. Results The median, range age of the cohort was (median 10, range 6-18.8 months). One-hundred thirteen (62.8%) were males, and 67 (37.2%) were females. The higher frequency of sepsis, ventilator-acquired pneumonia (VAP), and mortality founded in the group received PN. Frequency of sepsis was 15 (16.7%), VAP was 5 (5.6%), and the mortality rate was 11.1% in EN group, while frequency of sepsis was 37 (41.1%), VAP was 23 (25.6%), and the mortality rate was 27.8% in PN group (P = 0.001, 0.001, 0.01, respectively). Median of weight gain on the EN group was 0.17 kg at 2nd week which was more than those in PN group (P = 0.001). The mean ± SD time for reaching the caloric target for those receiving early EN was 4.0 ± 1.9 days which is earlier than that of PN group (6.2 ± 1.7 days) (P = 0.001). There is no significant difference between both groups as regard pediatric intensive care unit (PICU) stay length and mechanical ventilation stay length. Conclusion Early EN remains the preferred route for nutrient delivery as the PN route was accompanied by a lot of complication such as sepsis, VAP, and high mortality rate.